2007
DOI: 10.1002/chem.200700296
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Novel Sugar‐Substituted Bipyridine Complexes of Rhenium and 99m‐Technetium

Abstract: Novel ligands have been obtained from the reaction of 4,4'-dibromomethyl-2,2'-bipyridine with 2,3,4,6-tetra-O-acetyl-beta-D-glucopyranosylthiol, 2,3,4,6-tetra-O-acetyl-beta-D-galactopyranosylthiol or 2,3,4,6-tetra-O-acetyl-alpha-D-thioacetylmannopyranoside in which the sugar residues are thioglycosidically linked to the bipyridine in the 4,4'-position. Cleavage of the acetyl groups affords hydrophilic symmetric ligands with free hydroxyl groups. Reaction of the new glycoconjugated ligands (L) with [Re(CO)(5)Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 68 publications
2
38
1
Order By: Relevance
“…[2][3][4][5] The use of metalloglycoclusters as a probe molecule is an attractive proposition because the metal center furnishes photochemical and electrochemical properties that can be employed as useful analytical indicators in kinetic studies. Gottschaldt et al 6 reported on metalloglycoclusters that contain a rhenium or technetium metal center, and Kobayashi et al 2 and Kikkeri et al 3 reported on ruthenium metalloglycoclusters. Because the clusters can possess a variety of coordination numbers, in addition to providing useful photochemical and electrochemical properties, unique geometrical features can be imparted to the carbohydrate probe.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The use of metalloglycoclusters as a probe molecule is an attractive proposition because the metal center furnishes photochemical and electrochemical properties that can be employed as useful analytical indicators in kinetic studies. Gottschaldt et al 6 reported on metalloglycoclusters that contain a rhenium or technetium metal center, and Kobayashi et al 2 and Kikkeri et al 3 reported on ruthenium metalloglycoclusters. Because the clusters can possess a variety of coordination numbers, in addition to providing useful photochemical and electrochemical properties, unique geometrical features can be imparted to the carbohydrate probe.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported sugar-containing Ir(III) complex (1) is hardly soluble in benzene; thus, we synthesized a novel Ir(III) complex coordinated with bipyridyl ligands bearing acetyl-protected glucose by following a modified version of our reported method (Scheme 4) [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…The starting bipyridyl ligands bearing acetyl-protected glucose were prepared according to a reported method [9]. Bromomethyl-2,2′-bipyridine (160 mg, 0.47 mmol) was dissolved in DMF (2 mL), followed by the addition of 1-thio-β-D-glucose tetraacetate (350 mg, 0.97 mmol) and Na 2 CO 3 (350 mg, 3.3 mmol) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR and 13 C NMR spectroscopic data were identical to the literature. [8] The dichloro-bridged dimer [Ir(C N) 2 -μ-Cl] 2 was conveniently prepared from a reaction of the respective ligand and IrCl 3 ·xH 2 O.…”
Section: Resultsmentioning
confidence: 99%